A Study on the Quality of Doctoral Education Based on the IPOD Framework: A Case of Agriculture-Related Disciplines. Issue 3 (4th May 2018) - Luo, Yingzi; Liu, Zewen; Zhang, Jiale; Gu, Jianxiu
Abstract: Based on the input-process-output-development (IPOD) framework, a survey of current doctoral students and doctoral graduates from six agricultural universities in China found that doctoral students in agriculture have higher graduation delay rates, relatively consistent academic backgrounds, a longer learning input time, and fewer foreign research and teaching experiences, along with insufficient career guidance, and expectations for academic careers. Doctoral graduates have diversified career paths, but their jobs tend to match their specialty. The degree of fit between individuals and jobs is higher than that between individuals and employers. In addition, the satisfaction of current doctoral students is lower than that of doctoral graduates. The survey results indicate that the three-year doctoral education system is not well adapted to the needs of doctoral students, and appropriate adjustments to the length of study should be based on differences between disciplines. Doctoral students have a significant utilitarian motivation, and their rational understand should be enhanced; they also lack career preparation, and their career guidance should be strengthened.